Sistem Pendukung Keputusan Kebersihan Area Toilet Menggunakan Metode Fuzzy Tsukamoto - Firza Novianto; Sri Lestari (Syntax Corporation, 2023)
The cleanliness of the restroom is critical in keeping customers interested in returning. Therefore, maintaining the cleanliness of the toilet is important to provide comfort to customers. The toilet area is cleaned regularly by outsourced employees and then checked periodically by the relevant leader in the area to determine the level of cleanliness of the toilet. The design of the system in this study was carried out by making a sitemap, flowchart, database schema, table structure, and designing the user interface of the system to be built. Based on the results of the analysis and design of the best toilet determination system using the Tsukamoto fuzzy method, it can be concluded that the Tsukamoto fuzzy method can be used in determining the best toilet based on toilet data using 3 criteria, namely: toilet area, closet, and sink. The calculation results are determined from the rules used in fuzzy.